2013
DOI: 10.1007/s00384-013-1665-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inpatient exercise therapy on the length of hospital stay in stages I–III colon cancer patients: randomized controlled trial

Abstract: Low-to-moderate-intensity postsurgical exercise reduces length of hospital stay and improves bowel motility after colectomy procedure in patients with stages I-III colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 15 publications
2
96
0
2
Order By: Relevance
“…These precautions, however, should be balanced with evidence‐based mobilization and postoperative activity recommendations, and should be informed by surgical precautions and guidance. Mobility and exercise participation in the acute postoperative stage of treatment may reduce the risk of adverse events [6,7], affect overall length of stay [8], and reduce readmissions and complications in various cancer populations [6,9].…”
Section: Safety Considerations With Antineoplastic Treatment Adverse mentioning
confidence: 99%
“…These precautions, however, should be balanced with evidence‐based mobilization and postoperative activity recommendations, and should be informed by surgical precautions and guidance. Mobility and exercise participation in the acute postoperative stage of treatment may reduce the risk of adverse events [6,7], affect overall length of stay [8], and reduce readmissions and complications in various cancer populations [6,9].…”
Section: Safety Considerations With Antineoplastic Treatment Adverse mentioning
confidence: 99%
“…Despite these promising epidemiological data, only 6 randomized controlled exercise intervention trials have so far been conducted in this patient group. [10,11] Their findings include increases in physical fitness and a reduced length of hospital stay. One reason for the small number of studies might be that there is a huge uncertainty with regard to exercisability of CRC patients having an ostomy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exercise positively improves physical function and biomarkers related to colorectal cancer, such as insulin resistance, insulin-like growth factor (IGF)-1, tumor necrosis factor (TNF)-alpha, and adiponectin (Cheville et al, 2013;. It has also been found that exercise shortens the length of hospitalization and time to flatus even for inpatients who just underwent colorectal cancer surgery, which may improve long-term colorectal cancer prognosis (Ahn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%